2009
DOI: 10.1093/aob/mcp201
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission from natural wetlands: interplay between emergent macrophytes and soil microbial processes. A mini-review

Abstract: The role of the nitrogen cycle in repression of methane production is probably low. In contrast to wetlands particularly created for the purification of nitrogen-rich waste waters, concentrations of inorganic nitrogen compounds are low in the root zones in the growing season due to the nitrogen-consuming behaviour of the plant. Therefore, nitrate hardly competes with other electron acceptors for reduced organic compounds, and repression of methane oxidation by the presence of higher levels of ammonium will not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
275
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(290 citation statements)
references
References 106 publications
10
275
2
3
Order By: Relevance
“…Aquatic plant roots influence the activity of microorganisms through organic matter production and oxygen transportation to the rhizosphere (Garnet et al 2005). On the other hand, methane found in the sediment can be transported to the atmosphere across the macrophytes' aerenchyma tissues (Laanbroek, 2010), reducing gas consumption and carbon accumulation in the sediment. Although the amount of methane emitted into the atmosphere is just a relatively small proportion of the total C accumulated in the sediment, it can be significant in terms of global warming due to the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aquatic plant roots influence the activity of microorganisms through organic matter production and oxygen transportation to the rhizosphere (Garnet et al 2005). On the other hand, methane found in the sediment can be transported to the atmosphere across the macrophytes' aerenchyma tissues (Laanbroek, 2010), reducing gas consumption and carbon accumulation in the sediment. Although the amount of methane emitted into the atmosphere is just a relatively small proportion of the total C accumulated in the sediment, it can be significant in terms of global warming due to the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the CO 2 dynamics in coastal aquatic ecosystems, studies performed at the same system showed that it tends to be a consistent CO 2 source to the atmosphere (Marotta et al, 2009;2010). However, these studies did not evaluate the role of aquatic macrophytes gas transportation and alterations in the littoral zone to CO 2 dynamics.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…CH 4 and N 2 O emissions from wetlands are subjected to a number of biotic and abiotic controls Bridgham et al 2013), among which plants are considered to be the major one because they can strongly affect CH 4 and N 2 O production, consumption, and transportation (Rückauf et al 2004;Laanbroek 2010). Plant presence can increase soil CH 4 flux by enhancing substrate availability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plants can supply microbes with labile substrates and serve as a transport pathway, which may increase N 2 O emissions (Rückauf et al 2004;. Previous studies have reported increases (Bellisario et al 1999;Laanbroek 2010) or decreases (Kao-kniffin et al 2010;Sutton-Grier and Megonigal 2011) of CH 4 emission in response to an increase in plant biomass or productivity. The contribution of plant-mediated CH 4 flux varied substantially among species and wetland types (Whiting and Chanton 1992;Ding et al 2005;Dorodnikov et al 2011).…”
Section: Introductionmentioning
confidence: 99%